Profitability, Solvency, Dividend Policy and Their Influence on Industrial Sector Stock Prices (IDXINDUST) IDX-IC - Nainggolan, Helena Olivia Yosih Br.; Nawir, Jubaedah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is quantitative with the aim of knowing profitability, solvency, dividend policy and its effect on stock prices in the Industrial sector (IDXINDUST) IDX-IC. In the Industrial sector (IDXINDUST) IDX-IC experienced fluctuations in the value of profitability, solvency, dividend policy and stock prices. The sampling technique used slovin with an error margin of 5%. Based on the calculation of the slovin technique, it is known that a sample of 47 out of 54 companies registered in the Industrial Sector (IDXINDUST) IDX-IC. The hypothesis test in this study used the T test. The data in this study included panel data so as to find out the panel data regression and the T test used Eviews 10. Profitability in this research was measured by Net Profit Margin (NPM). Solvency in this research is measured by Debt to Asset Ratio (DAR). Dividend policy in this research is measured by the Dividend Payout Ratio (DPR). Based on the results of this study, it can be seen that (1) Profitability has a positive effect on stock prices (2) Solvency has no effect on stock prices (3) Dividend policy has a positive effect on stock prices.